Should an increase in cerebral neurochemicals following head kicks in full contact karate influence return to play?. (December 2015) - Graham, MR; Pates, J; Davies, B; Cooper, SM; Bhattacharya, K; Evans, PJ; Baker, JS
Background: Cerebral neurochemicals are markers of traumatic brain injury (TBI). Objectives: The aim of the study was to determine whether kicks to the head (KTH) in full contact karate significantly increased serum concentrations of protein S-100B, and neurone specific enolase (NSE). Kicks to the body (KTB) were also quantified to asses muscle tissue injury. Muscle damage was assessed by analysis of serum total creatine kinase (CK). Methods: Twenty-four full contact karate practitioners were observed and filmed during actual competition and divided into two main groups post event: (1) Kicks to the head and body group (KTH): n = 12; mean ± SD; age, 30.4 ± 6.7 years; height, 1.74 ± 0.1 m; weight, 79.1 ± 2.1 kg; and (2): Kicks to the body group (KTB): n = 12; mean ± SD; age, 28.2 ± 6.5 years; height, 1.75 ± 0.1 m; weight, 79.2 ± 1.7 kg. The KTH group received direct kicks to the head, while group KTB received kicks and punches to the body. Blood samples were taken before and immediately post-combat for analysis of serum S-100B, NSE, CK and cardiac troponin. Results: Significant increases in serum concentrations of S-100B (0.12 ± 0.17 vs. 0.37 ± 0.26, µg.L −1 ) and NSE (11.8 ± 4.1 vs. 20.2 ± 9.1 ng.mL −1 ) were encountered after combat in the KTH group and CK (123 ± 53 vs. 184 ± 103 U.L −1 ) in the KTB group (all P <0.05). Conclusions: Head kicks in full contact karate cause elevation of neurochemical markers associated with damaged brain tissue. The severity of injury is related to the early post-traumatic release of protein S-100B and NSE. The early kinetics and appearance post injury can reflect intracranial pathology, and suggest S-100B and NSE are extremely sensitive prognostic markers of TBI.